Validity of the Hum Test, a Simple and Reliable Alternative to the Weber Test. (June 2018) - Ahmed, Omar H.; Gallant, Sara C.; Ruiz, Ryan; Wang, Binhuan; Shapiro, William H.; Voigt, Erich P.
Objectives: To compare the diagnostic performance of the Hum Test against the Weber Test using pure tone audiometry (PTA) as the "gold standard" comparator. Methods: 29 participants with normal hearing of ages 18 to 35 without any history of hearing abnormalities or otologic conditions were enrolled. Subjects underwent three tests (Hum Test, Weber Test, and PTA) across two conditions: with an ear plug in one ear (side randomized) and without ear plugs. Results: When examining the ability of the Hum Test to detect simulated conductive hearing loss (CHL), the test had a sensitivity of 89.7% and specificity of 100% with high pitched humming and 93.1% and 100%, respectively, with low pitched humming. The Weber Test had a sensitivity and specificity of 96.6% and 100%, respectively. McNemar's test demonstrated agreement between the Hum Test, performed with either high pitched ( P = .32) or low pitched ( P = .56) humming, and the Weber Test. Receiver operating characteristic (ROC) curves for the Hum Test (both high and low pitched) and Weber test were compared and demonstrated no statistically significant difference. Conclusion: The Hum Test is comparable to the Weber Test with regards to its sensitivity, specificity, and diagnostic accuracy in assessing new onset unilateral CHL in previously normal hearing subjects.